2022
DOI: 10.1002/cche.10581
|View full text |Cite
|
Sign up to set email alerts
|

Gluten‐free traditional Turkish noodle with Macrolepiota procera mushroom: Functional, textural, thermal and sensory characteristics

Abstract: Background and Objectives The powder of dried Macrolepiota procera was used in gluten‐free (GF) Turkish noodle production by substituting rice flour (RF), in the ratios of 0%, 5%, 10%, and 15% for the fortification of traditional egg pasta (erişte). Findings Cooking was responsible for decreasing brightness, redness‐blueness, and hardness in all samples when compared to unboiled ones. Declines in the amount of RF in formulation enhanced ash (from 0.749% to 1.247%), protein (from 12.688% to 18.063%), mineral, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…The recipe of the Süfer was followed for gluten-free noodle production with a slight modification [29]. PSF, OSF, and GFF in amounts of 100 g were mixed at different rates with 40 g of whole egg, 0.5 g of table salt, and finally, 20-23 mL of water, which was added based on dough consistency.…”
Section: Development and Optimization Of Noodle Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The recipe of the Süfer was followed for gluten-free noodle production with a slight modification [29]. PSF, OSF, and GFF in amounts of 100 g were mixed at different rates with 40 g of whole egg, 0.5 g of table salt, and finally, 20-23 mL of water, which was added based on dough consistency.…”
Section: Development and Optimization Of Noodle Formulationmentioning
confidence: 99%
“…Gluten-free noodles prepared with different rates of flours, salt, and water were given a sensory evaluation for overall acceptability, hardness, stickiness, taste, chewiness, and color on a 5-point hedonic scale from 1 = extremely bad to 5 = most excellent by 21 trained panelists. The panelists consisted of academicians, postgraduate students, and administrative staff of Suleyman Demirel University, who took a brief lesson about drinking water between tastings, swallowing, chewing, and the time required for this process [29,30]. Noodles were served on a white plate that was coded with three random, single-digit numbers.…”
Section: Sensory Analysismentioning
confidence: 99%
“…When the studies on glutenfree noodle production were examined, it was found that amaranth, buckwheat, and quinoa flour blends were added to wheat flour on a substitution basis max. 30%, [10], buckwheat flour, rice flour, and corn starch combinations [11], Macrolepiota procera mushroom by substituting rice flour [12], quinoa and quinoa + buckwheat blends [14], and chia flour by substituting rice flour: corn starch [13] were used. When the studies were examined, although there were studies on pasta produced by adding a small amount of wheat flour, no study was found on the use of quinoa in making gluten-free eris ¸te.…”
Section: Introductionmentioning
confidence: 99%